Quantifying maternal antibody transfer to colostrum and cord blood reveals virus-specific selectivity in dogs - Teh, Serena S.; Truyen, Lotta H.; Woodyear, Sarah; Palmeri, Jessica; Pimenta-Pereira, Ana Alice; Peprah, Alexis A. E.; Lanman, Ella; Lonergan, Tom M.; Reid, Abigail; Cheong, Soon Hon; Caddy, Sarah L. (Frontiers in Immunology, 2026)
BackgroundNeonatal infections are a leading cause of mortality in dogs, with up to 30% of puppies dying within the first 3 weeks of life. During this critical period of immune development, protection is highly dependent on maternal antibodies (MatAbs) transferred across the placenta and via colostrum. Despite the critical importance of this transfer, limited information is available regarding the biological or clinical factors that determine its magnitude, whether specific antibodies are preferentially transferred, or how these processes vary across a broad population of dogs.MethodsTo quantify and explore the determinants of MatAb transfer in dogs, we analyzed matched maternal serum, cord blood, and colostrum samples collected from 44 client-owned dams undergoing cesarean section at a university veterinary hospital. Total immunoglobulin G (IgG) and virus-specific antibodies against canine parvovirus (CPV) and canine distemper virus (CDV) were analyzed. We also evaluated the influence of maternal factors, including age, breed, body weight, parity, and litter size, on MatAb transfer efficiency.ResultsAcross this diverse population, we observed limited transplacental transfer of MatAbs (4.5%–6% of the maternal titer), consistent with previous studies and as expected given the endotheliochorial placenta of dogs. In contrast, virus-specific IgG was highly enriched in colostrum, with 10.7-fold (CPV) and 8.1-fold (CDV) increases relative to serum. Transfer efficiency was significantly greater for virus-specific antibodies than for total IgG (3.2-fold), suggesting selective enrichment of antiviral antibodies during colostrogenesis. Maternal serum antibody titer emerged as the primary factor influencing antibody transfer efficiency.ConclusionsThese findings provide the most comprehensive quantification to date of MatAb transfer routes in dogs, revealing preferential transfer of virus-specific IgG to colostrum and highlighting the crucial role of colostrum intake in neonatal immunity. This work establishes a foundation for identifying antibody characteristics that influence MatAb transfer efficiency and reinforces the importance of ensuring that dams have adequate titers of virus-specific IgG prior to breeding.